2016
DOI: 10.14814/phy2.12892
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise within lower body negative pressure protects leg lean tissue mass and extensor strength and endurance during bed rest

Abstract: Leg muscle mass and strength are decreased during reduced activity and non‐weight‐bearing conditions such as bed rest (BR) and spaceflight. Supine treadmill exercise within lower body negative pressure (LBNPEX) provides full‐body weight loading during BR and may prevent muscle deconditioning. We hypothesized that a 40‐min interval exercise protocol performed against LBNPEX 6 days week−1 would attenuate losses in leg lean mass (LLM), strength, and endurance during 6° head‐down tilt BR, with similar benefits for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…Fourty five studies specified a time period ahead of the bed rest period in which baseline measures were recorded ranging from 1 to 21 days. Of these, 11 (Greenleaf et al, 1983, 1989, 1994b; Dudley et al, 1989; Ellis et al, 1993; Ferrando et al, 1995; Portero et al, 1996; Muir et al, 2011; Lee et al, 2014; English et al, 2016; Schneider et al, 2016) stated utilizing a pre-bed rest ambulatory control period in their methods section. However, it was not clear in any of the studies what the control period involved or if there was any pre-bed rest deconditioning that was measured or adjusted for.…”
Section: Resultsmentioning
confidence: 99%
“…Fourty five studies specified a time period ahead of the bed rest period in which baseline measures were recorded ranging from 1 to 21 days. Of these, 11 (Greenleaf et al, 1983, 1989, 1994b; Dudley et al, 1989; Ellis et al, 1993; Ferrando et al, 1995; Portero et al, 1996; Muir et al, 2011; Lee et al, 2014; English et al, 2016; Schneider et al, 2016) stated utilizing a pre-bed rest ambulatory control period in their methods section. However, it was not clear in any of the studies what the control period involved or if there was any pre-bed rest deconditioning that was measured or adjusted for.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies should assess the effect of nutrition, together with exercise, on muscle and hemodynamic parameters during bedrest immobilization. This is important as physical activity has been singly identified as an important intervention in preventing deleterious effects of bedrest confinement 60,61 . Additional interventions that could be tested include cognitive training 21 , LBNP 62 , and artificial gravity 63 ; all of these have been shown to alleviate the symptoms of bedrest induced physiological deconditioning.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…The current constraint bungee cord in space flight is an elastic material, implying that the constraint loading changes linearly with the body height during running. However, previous studies proposed that a constant constraint loading may better prevent the musculoskeletal decline in spaceflight [ 14 , 25 ], which could be achieved by manipulating the loading devices. Second, the kinematical data of treadmill exercise at gravity was also used to drive the musculoskeletal model at weightlessness, because weightless experiment has reported that the gait at weightlessness approached to the gait at gravity when the resultant constraint force increased to body weight on earth.…”
Section: Discussionmentioning
confidence: 99%
“…In the weightless condition, bungee cords were applied instead of gravity to constrain the body on the treadmill during exercise. Previous studies have suggested that providing a constraint force equal to gravity could better prevent musculoskeletal decline in spaceflight [ 14 , 25 ]. Therefore, in the present study, the resultant force of the bungee cords was assumed to be constantly equal to gravity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation